2022
DOI: 10.3390/land11040575
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Grassland Restoration—A South African Perspective

Abstract: The principal drivers of Grassland Biome conversion and degradation in South Africa include agricultural intensification, plantation forestry, urban expansion and mining, together with invasive non-native plants and insidious rural sprawl. This biome is poorly conserved and in dire need of restoration, an ecologically centred practice gaining increasing traction given its wide application to people and biodiversity in this emerging culture of renewal. The pioneering proponent of restoration in South Africa is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 130 publications
3
15
0
Order By: Relevance
“…While birds were partly migratory and resident in behavior, all mammals foraged at a central place, complemented by birds that disperse seeds over relatively longer distances in this study (Table 1). Our finding that 39% of the natural habitat has been transformed confirmed previous reports (e.g., Carbutt & Kirkman, 2022;Matsika, 2008;O'connor & Kuyler, 2009;Skowno et al, 2019) showing that agricultural production, human settlement, and mining activities have reduced the space available for O. europaea subsp. africana population in the Grassland Biome.…”
Section: P Otential S Eed D Is Per Sal Dis Tan Ce Ssupporting
confidence: 92%
See 1 more Smart Citation
“…While birds were partly migratory and resident in behavior, all mammals foraged at a central place, complemented by birds that disperse seeds over relatively longer distances in this study (Table 1). Our finding that 39% of the natural habitat has been transformed confirmed previous reports (e.g., Carbutt & Kirkman, 2022;Matsika, 2008;O'connor & Kuyler, 2009;Skowno et al, 2019) showing that agricultural production, human settlement, and mining activities have reduced the space available for O. europaea subsp. africana population in the Grassland Biome.…”
Section: P Otential S Eed D Is Per Sal Dis Tan Ce Ssupporting
confidence: 92%
“…Grasslands are threatened by fragmentation, which involves the splitting of natural habitats into smaller isolated patches primarily by human disturbances such as land clearing for human settlement (Bredenkamp et al, 2006 ; Carbutt & Kirkman, 2022 ; Matsika, 2008 ; Neke & du Plessis, 2004 ; Skowno et al, 2019 ; Vukeya et al, 2023 ), agricultural activities (Matsika, 2008 ; Nkuekam et al, 2018 ; Turpie et al, 2007 ), and mining activities (Brown & du Preez, 2014 ; Olivier, 2020 ). Several studies have reported that 40% of the grassland biome has been irrevocably modified while 60% of remaining grassland areas are threatened as they are losing an important aspect of their composition, structure, and function (Little et al, 2015 ; Neke & du Plessis, 2004 ; SANBI, 2013 ; Skowno et al, 2019 ), which may need urgent restoration for biodiversity conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Our assessment of the magnitude of grassland cover changes at the subcontinent level revealed mixed findings. Carbutt et al, 2011;Brown and Bezuidenhout, 2020;Carbutt and Kirkman, 2022). There are possibilities that climate change also contributed to the reduction in the grassland biome in Southern Africa (Brown and Bezuidenhout, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the increasing human activities, such as agricultural intensification (O'Connor and Kuyler, 2009), afforestation (Bond et al, 2019), urban sprawling (Yao et al, 2019;Puplampu and Boafo, 2021), mining (Carbutt and Kirkman, 2022), indiscriminate grazing (Wachiye et al, 2022) and burning activities in Africa (Tarimo et al, 2015;Bond, 2016;Dwomoh and Wimberly, 2017) could jointly or independently disrupt grassland ecosystems. The impacts of the recent and future climate changes and anthropogenic activities on grasslands are gradual processes that should be monitored through time and space for an in-depth understanding of the processes driving changes in African grasslands (Hobbie et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the functional attributes of each ecosystem, it is necessary to give consideration to both ecological protection and production practices (Bengtsson et al, 2019). However, although we know that restoration strategies for degraded grasslands should be tailored to local conditions (Liu et al, 2019;Carbutt and Kirkman, 2022;Lyu et al, 2022), human interventions for grassland restoration tend to consider the single ecological (diversity) or productive (biomass) functions of grasslands (Guo, 2007). Moreover, the functions of grasslands have also changed during different restoration stages, which requires us to adjust strategies in time and respond flexibly.…”
Section: Introductionmentioning
confidence: 99%